Here's the question you clicked on:
my-geek-pride
Use trig identites to transform the left side of equation into the right. (1+cos theta)(1-cos theta)= sin^2theta
1+cos theta =2cos^2 theta/2
multiply on the left, and get \[1-\cos^2(\theta)\] then it should be easy enough
1-cos theta=2sin^2 theta/2
is it clear that \[1-\cos^2(\theta)=\sin^2(\theta)\]?
ooohh. yea. I see.
"Welcome to OpenStudy. I can guide regarding this useful site; ask your doubts from me, for it you can message me. Please use the chat for off topic questions. And remember to give the helper a medal, by clicking on "Best Answer". We follow a code of conduct, ( http://openstudy.com/code-of-conduct ). Please take a moment to read it."
use identity ---> a^2 - b^2 for lhs then prove using cos2 + sin2 = 1
(1+cosθ)(1−cosθ)=(1−cosθ+cosθ−cos2θ) = sin2theta